Cisplatin increases PD-L1 expression and optimizes immune check-point blockade in non-small cell lung cancer. (1st November 2019) - Fournel, Ludovic; Wu, Zherui; Stadler, Nicolas; Damotte, Diane; Lococo, Filippo; Boulle, Geoffroy; Ségal-Bendirdjian, Evelyne; Bobbio, Antonio; Icard, Philippe; Trédaniel, Jean; Alifano, Marco; Forgez, Patricia
Abstract: The number of clinical protocols testing combined therapies including immune check-point inhibitors and platinum salts is currently increasing in lung cancer treatment, however preclinical studies and rationale are often lacking. Here, we evaluated the impact of cisplatin treatment on PD-L1 expression analyzing the clinicopathological characteristics of patients who received cisplatin-based neoadjuvant chemotherapy followed by surgery and showed that cisplatin-based induction treatment significantly increased PD-L1 staining in both tumor and immune cells from the microenvironment. Twenty-two patients exhibited positive PD-L1 staining variation after neoadjuvant chemotherapy; including 9 (23.1%) patients switching from <50% to ≥50% of stained tumor-cells. We also confirmed the up-regulation of PD-L1 by cisplatin, at both RNA and protein levels, in nude and immunocompetent mice bearing tumors grafted with A549, LNM-R, or LLC1 lung cancer cell lines. The combined administration of anti-PD-L1 antibodies (3 mg/kg) and cisplatin (1 mg/kg) to mice harboring lung carcinoma significantly reduced tumor growth compared to single agent treatments and controls. Overall, these results suggest that cisplatin treatment could synergize with PD-1/PD-L1 blockade to increase the clinical response, in particular through early and sustainable enhancement of PD-L1 expression. Highlights: Cisplatin-based induction chemotherapy increases PD-L1 expression by tumor cells. PD-L1 staining of microenvironment immune cells was higher after neoadjuvant treatment. Cisplatin rapidly increases PD-L1 mRNA and protein levels in lung cancer cell lines. In tumor bearing mice injection of cisplatin significantly enhances PD-L1 expression. The combined treatment associating cisplatin and anti-PD-L1 improves tumor response.